Konut yapı kooperatiflerinde güven ilişkisi ve yeni bir yaklaşım: Fonksiyonel değişim modeli - (:unkn) unknown (My University, 2012)
Güven, bireyler için temel bir ihtiyaçtır. Örgütlerle bireyler arasındaki bağların temelini güven oluşturmaktadır. Kooperatif örgütlerde ise güven, birden fazla değişkeni birbirine bağlamaktadır. Birey ekonomilerinin bir araya gelerek oluşturduğu kooperatif gruplar, kooperatif örgütten ihtiyaçları olan güveni sağladıkları takdirde kooperatif etkiye ulaşabilirler. Bu çalışmada Konut Yapı Kooperatiflerinde güven ilişkisi araştırılmış ve bu kooperatiflerde güven ihtiyacının maksimum düzeyde karşılanabilmesi için örgüt yapısı ve işleyişine dair yeni bir yaklaşım olan Fonksiyonel Değişim Modeli sunulmuştur. Araştırmada dördü bağımsız, üçü bağımlı toplam yedi temel değişken incelenerek dokuz hipotez oluşturulmuştur. Çalışma sonucunda yedi hipotez desteklenmiş, iki hipotez ise reddedilmiştir. Araştırmadan elde edilen bulgulara göre konut yapı kooperatiflerinde güven düzeyinin düşük olduğu saptanmıştır.

Trust is an essential need for individuals. Trust forms the basis of the relationship between organizations and individuals. In cooperative organizations, trust connects more than one variables. If cooperative groups, which are formed by coming together individual economies, provide the trust from cooperative organizations, they can attain the cooperative effect. In this study, trust relationship in housing cooperatives was researched. And presented model of functional alternation, which is a new approach, to organizational structure and functioning of in order to meet confidence need at maximum level in this cooperatives. In the research, nine hypotheses was formed by analysing seven basic variable, four of them independent and three of them depended. At the end of the research, seven hypotheses were supported and two hypotheses were rejected.It was found that, trust in housing cooperatives has an expressive relationship with marketing activites , loyalty, importance of activites and obtained performance. According to findings, trust to directors in housing cooperatives is at low levels. This result affected the partner's loyalty to cooperatives and the thoughts about being reference.
Trust correlation in housing cooperatives and a new approach: A model of functional alternation
Keywords: İktisat; İşletme